Implementation of halal certification in ensuring local food security in the global market - Abdullah, Syarif; Erwin, Erwin; Wiyono, Slamet; Susilo, Sidik; Mursyidah, Himmatul; Ikhsan, Fajri; Asmaraningtyas, Kinanthi Trah; Selina, Novalia Qoiri Putri (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2024)
Local food security must be continuously improved to compete in the global market. In addition to boosting income, local food products must ensure their halal certification. Halal certification institutions play a crucial role in guaranteeing product halalness. However, many micro, small, and medium enterprises (MSMEs) need to be made aware of the certification process, despite legal requirements mandating that all products in Indonesia be halal certified, including MSME products. This study explores the implementation of halal certification to support local food security in the global market. Data were gathered through literature reviews, direct observations, and interviews with MSMEs in Cilegon City, Banten, Indonesia. The study included workshops and ongoing assistance through the Untirta Halal Center to guide MSMEs in completing the halal certification process. The findings indicate that halal certification strengthens local food security and enhances the competitiveness of local products in the global market. Ketahanan pangan lokal perlu terus ditingkatkan agar mampu bersaing di pasar global. Selain sebagai upaya meningkatkan pendapatan, produk pangan lokal juga harus memastikan kehalalannya melalui sertifikasi yang sesuai. Lembaga sertifikasi halal berperan penting dalam memberikan jaminan kehalalan produk. Namun, masih banyak pelaku usaha mikro, kecil, dan menengah (UMKM) yang belum sepenuhnya memahami proses sertifikasi, meskipun peraturan mewajibkan semua produk di Indonesia, termasuk produk UMKM, memiliki sertifikat halal. Penelitian ini menganalisis penerapan sertifikasi halal sebagai langkah strategis untuk memperkuat ketahanan pangan lokal dalam menghadapi persaingan pasar global. Data dikumpulkan melalui kajian pustaka, observasi lapangan, dan wawancara dengan pelaku UMKM di Kota Cilegon, Banten. Penelitian ini mencakup pelaksanaan lokakarya serta pendampingan intensif melalui Halal Center Untirta, yang membantu UMKM menyelesaikan proses sertifikasi halal. Hasil penelitian menunjukkan bahwa sertifikasi halal tidak hanya memperkuat ketahanan pangan lokal, tetapi juga meningkatkan daya saing produk lokal di pasar global.